Geography science strategy to increase students' interest in learning with the help of digital-based learning media - Beni Lidiawati; Muhammad Nurwahidin; Sugeng Widodo (ARKA INSTITUTE, 2022)
Today's education mostly uses digital-based media, without exception. The use of information and communication technology media makes it easy for teachers to convey messages to students. This study aims to provide input to Geography subject teachers in designing learning strategies to increase students' interest in learning with the help of digital-based learning media. This study uses the SLR method used to identify, review, evaluate, and interpret all available research with topic areas of interest to phenomena, with certain relevant research questions. By using the SLR method, a systematic review and identification of journals can be carried out. To complete this research, researchers collected journal articles from Google Schoolar, Research Gate, SINTA, DOAJ, and Scopus. Based on some of the research that has been described, it can be concluded that digital-based learning media has an influence on students' learning interest, with the development of learning media it is hoped that teachers can innovate and be creative in the process of delivering messages to students with fun digital-based learning.